To analyse the suitability of a set of soical and economic indicators that assesses the impact on SI enhancing advanced technological inputs by farming households in Punjab Pakistan - Muhammad Bilal; Jan Barkmann; Tinoush Jamali Jaghdani (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
Increase in agricultural production in industrialized and developing countries are based on the adoption of new and improved technologies. Farming household's social and economic conditions greatly determines the adoption of new technologies. Particularly in developing countries majority of farming community comprises by small farming households. Pakistan is very interesting case in developing countries as its economy is based on agriculture and smallholder's production system is the salient characteristics of its farming community. The study in hand is conducted to examine the role of social and economic indicators which assesses the adoption of sustainable intensification-enhancing advance technologies in Pakistan. The study was conducted in Punjab province because it is the major contributor in agricultural GDP. The logit model is employ for the empirical findings of initial survey. A logit estimate shows that both social and economic indicators have statistically significant association with the adoption decision.
Keywords: 330; sustainable intensification; smallholders; adoption decision; Punjab